Infective Endocarditis of Pulmonary valve and arterial wall - Khanal, Hari har (Nepalese Heart Journal, 2006)
21 years old married girl presented with shortness of breath for last 2-3 years slightly and more increased in intensity for last 5-6 months, more marked on lying position; fever, chills, rigor and sweating present mostly at night time for last 2-3 months; chest pain which was located at the center of the chest and radiating to the back.